Premorbid Clinical Frailty Score and 30‐day mortality among older adults in the emergency department - Ji Young Huh; Yoshinori Matsuoka; Hiroki Kinoshita; Tatsuyoshi Ikenoue; Yosuke Yamamoto; Koichi Ariyoshi (Journal of the American College of Emergency Physicians Open)
Abstract Objectives The association between frailty and short‐term prognosis has not been established in critically ill older adults presenting to the emergency department. We sought to examine the association between premorbid frailty and 30‐day mortality in this patient population. Methods This is a retrospective observational study on older adults aged over 75 who were triaged as Level 1 resuscitation with subsequent admissions to intermediate units or intensive care units (ICUs) in a single critical care center, from January to December 2019. We excluded patients with out‐of‐hospital cardiac arrest or those transferred from other hospitals. Frailty was evaluated by the Clinical Frailty Scale (CFS) from the patients’ chart reviews. The primary outcome was 30‐day mortality, and we examined the association between frailty scored on the CFS and 30‐day mortality using a multivariable logistic regression model with CFS 1–4 as a reference. Results A total of 544 patients, median age: 82 years (interquartile rang 78 to 87), were included in the study. Of these, 29% were in shock and 33% were in respiratory failure. The overall 30‐day mortality was 15.1%. The adjusted risk difference (95% confidence interval [CI]) in mortality for CFS 5, CFS 6, and CFS 7–9 was 6.3% (‐3.4 to 15.9), 11.2% (0.4 to 22.0), and 17.7% (5.3 to 30.1), respectively; and the adjusted risk ratio (95% CI) was 1.45 (0.87 to 2.41), 1.85 (1.13 to 3.03), and 2.44 (1.50 to 3.96), respectively. Conclusion The risk of 30‐day mortality increased as frailty advanced in critically ill older adults. Given this high risk of short‐term outcomes, ED clinicians should consider goals of care conversations carefully to avoid unwanted medical care for these patients.